Kleinstädte – Förderprogramme und Forschungsinitiativen. - Porsche, Lars (My University, 2021)
Förderprogramme und Forschungsinitiativen des Bundes und der Länder spielen für alle Städte und Gemeinden eine wichtige Rolle zur Vernetzung mit anderen Kommunen und zur Generierung neuen Wissens wie auch neuer Ansätze für eine zukunftsfähige Stadtentwicklung. Der Ad-hoc-Arbeitskreis „Kleinstadtforschung“ konstatierte das Fehlen von Forschungs- wie Programmförderung zu Kleinstädten. Der Beitrag stellt eine Auswahl an Programmen und Initiativen vor diesem Hintergrund dar und versucht zu hinterfragen, ob eine spezifisch auf Kleinstädte ausgerichtete Forschung und Förderung notwendig ist.

Funding programs and research initiatives by the German federation and federal states play an important role for all towns and municipalities, especially in terms of networking with other municipalities, generating new knowledge and also new approaches to sustainable urban development. The ad-hoc working group ‘Small town research’ established that there is a lack of research funding and programmatic finance for small towns. This article therefore examines selected programs and initiatives and attempts to determine whether research and funding specifically targeting small towns are necessary.
Small towns – Funding programmes and research initiatives.
Keywords: Kleinstadt; Städtebauförderung; Förderprogramm; Forschungsprogramm; Forschungsförderung; Stadtforschung; Forschungsbedarf